Partner-focused obsessions and self-esteem: An experimental investigation. (December 2015) - Doron, Guy; Szepsenwol, Ohad
Abstract: Background: Relationship-related obsessive-compulsive phenomena (ROCD) are encountered frequently in the clinic, and involve severe consequences to personal and relational well-being. One common presentation of ROCD involves disabling preoccupation and doubts focusing on intimate partner's flaws (partner-focused obsessions). It was previously suggested that individuals perceiving their partner's failures or flaws as reflecting on their own self-worth may be more sensitive to intrusive thoughts pertaining to their partner's qualities and characteristics. In the current studies, we assessed the link between partner-focused OC symptoms and self-esteem contingent on partner-value. Methods: In two studies we assessed the impact of experimentally induced partner-focused intrusions on self-esteem. In Study 1, we assessed individuals' self-esteem after one of three primes: (a) intrusion about one's partner comparing unfavorably with others of the same sex (i.e., alternative partners), (b) intrusion about one's partner comparing unfavorably to oneself, (c) and a neutral prime. In study 2, we tried to replicate Study 1 using a pre-post design and also examine whether favorable intrusions of one's partner would have an opposite effect on self-esteem than unfavorable intrusions. Results: Compared with the other groups, participants who were primed with intrusions of their partner being unfavorably compared to others reported lower self-esteem, but only if they had high levels of partner-focused symptoms. Favorable intrusions of partner to others did not have a positive effect on self-esteem among individuals with high levels of partner-focused symptoms. Conclusions: Partner-value self-sensitivity may be one of the perpetuating mechanisms involved in partner-focused OC phenomena. Highlights: Partner-focused OC symptoms are associated with self-esteem (SE) sensitivity to negative partner-related intrusive thoughts. Priming negative partner-related intrusions decreased SE only in individuals with high partner-focused symptoms. Such SE sensitivity may perpetuate the ROCD symptom cycle. Treatments addressing such sensitivities may prove useful when treating Partner focused OC phenomena.